2019
DOI: 10.3389/fneur.2019.00807
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Link Between Hyperhomocysteinemia and Ceramide Metabolism in Alzheimer-Type Neurodegeneration

Abstract: Aging is one of the strongest risk factor for Alzheimer's disease (AD). However, several data suggest that dyslipidemia can either contribute or serve as co-factors in AD appearance. AD could be examined as a metabolic disorder mediated by peripheral insulin resistance. Insulin resistance is associated with dyslipidemia, which results in increased hepatic ceramide generation. Hepatic steatosis induces pro-inflammatory cytokine activation which is mediated by the increased ceramides production. Ceramides levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 114 publications
0
20
0
Order By: Relevance
“…Increased tCho relative to tCr has been attributed to the cerebral infarctions, inflammation and multiple sclerosis [ 51 , 55 ]. It was recently shown that tCho was associated with the membrane turnover, which was directly related to Hcy removal [ 54 ], and a link between hHcy and ceramide metabolism was revealed in the AD-type neurodegeneration [ 52 , 56 ]. In our experiments, we did not find significant changes, neither in the levels of tCho nor the tCr, at any reperfusion time.…”
Section: Discussionmentioning
confidence: 99%
“…Increased tCho relative to tCr has been attributed to the cerebral infarctions, inflammation and multiple sclerosis [ 51 , 55 ]. It was recently shown that tCho was associated with the membrane turnover, which was directly related to Hcy removal [ 54 ], and a link between hHcy and ceramide metabolism was revealed in the AD-type neurodegeneration [ 52 , 56 ]. In our experiments, we did not find significant changes, neither in the levels of tCho nor the tCr, at any reperfusion time.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tCho is typically elevated during myelin sheet degradation [17,25] and an increase in tCho relative to tNAA and tCr was correlated with cerebral infarctions, ongoing gliosis, and ischemic and re/de-myelinization processes [19,25]. It was recently shown that tCho was associated with membrane turnover that was directly related to Hcy removal [24], and a link was revealed between hHcy and ceramide metabolism in AD-type neurodegeneration [17,25,26]. In our experiments, we did not find significant changes in the levels of tCho and tCr in the hippocampus, but the rise in its ratio suggests for the proposed process of hippocampal re/de-remyelination, neuroglial dyshomeostasis, and cell membrane turnover in MDG conditions.…”
Section: Metabolic and Volumetric Changes In The Hippocampus After Mementioning
confidence: 99%
“…Relevantly, De Wit et al (117) demonstrated that the in frontotemporal lobar dementia ceramide production in reactive astrocytes is independent of enhanced levels of aSMase but is due to an increase in the expression of CerS. It was observed also in AD (118). In this context it is very important to investigate changes in the SphL profile in the brain of animals with NDDinduced, and in CFS and blood of NDD patients during the course of this disease and its treatment.…”
Section: Discussionmentioning
confidence: 99%